Pengaruh Manajemen Kebersihan Menstruasi Dengan Pembelajaran Flex Model Dan Station Blended Learning Terhadap Persepsi Dan Perilaku Personal Hygiene Saat Menstruasi Pada Remaja Putri - Hidayati, Ariza Melinda; Puspitasari, Yenny; Widyowati , Agustin (Jurnal Locus Penelitian dan Pengabdian, 2025)
Introduction: The low awareness and practice of Menstrual Hygiene Management in adolescent girls results in a negative impact on reproductive health. Blended Learning is used as a learning and health education method in the digital revolution era. The purpose of this study is to analyze the effect of menstrual hygiene management with flex model learning and station rotation blended learning on the perception and behavior of personal hygiene during menstruation in adolescent girls. Method: This was a true-experimental study with a randomized pretest-posttest control group design. The sample consisted of two intervention groups and one control group, each with 34 respondents. The sampling method used simple random sampling and a questionnaire as the measuring instrument. The statistical test used a paired sample t-test with an ? value of <0.05. Result And Analysis: There is a significant influence between before and after menstrual hygiene intervention with flex model learning with a correlation value of 0.399 (moderate correlation relationship) and menstrual hygiene management intervention with station blended learning with a correlation value of 0.739 (very strong correlation relationship) on the perception of personal hygiene during menstruation in adolescent girls. There is a significant influence between before and after menstrual hygiene management with flex model learning with a correlation value of 0.559 (strong correlation relationship) and menstrual hygiene management intervention with station blended learning with a correlation value of 0.843 (very strong correlation relationship) on personal hygiene behavior during menstruation in adolescent girls. Conclusion: Health education using the blended learning method is expected to raise awareness and improve Menstrual Hygiene Management practices among adolescent girls.